Selected stem cell populations in pediatric acute lymphoblastic leukemia - Krętowska-Grunwald, Anna; Sawicka-Żukowska, Małgorzata; Starosz, Aleksandra; Krawczuk-Rybak, Maryna; Moniuszko, Marcin; Grubczak, Kamil (Frontiers in Immunology, 2024)
Acute lymphoblastic leukemia is characterized by a disturbed maturation of hematopoietic stem cells (HSCs) resulting in development of a malignant clone. Despite relatively positive outcome, there are still instances of disease relapse occurring due to ineffective disease eradication or primary leukemic clone alterations. Unclear significance of stem cells in the course of ALL led us to investigate and establish crucial changes in two stem cell populations -very small embryonic-like stem cells (VSELs) and HSCs during the induction phase of treatment. In a retrospective study selected stem cells in peripheral blood and bone marrow of 60 pediatric ALL subjects and 48 healthy controls were subjected to flowcytometric analysis at 4 different time points. Both VSELs and HSCs were elevated at the moment of ALL diagnosis compared to healthy controls, but profoundly decline until day 15. Further observations revealed an increase in HSCs with a concomitant depletion of VSELs until week 12. ALL patients with high HSCs showed positive correlation with bone marrow blasts at diagnosis. Patients with lower VSELs or HSCs at diagnosis had slightly improved response to applied therapy. We observed higher initial bone marrow lymphoblast values in patients with lower VSELs or higher HSCs in the high-risk group. The significance of VSELs in predicting treatment outcome can be illustrated by lower day 15 MRD level of patients with lower VSELs at diagnosis. In conclusion, we found HSCs and VSELs to be valid participants in pediatric ALL with possible contribution in the neoplastic process and prediction of initial treatment outcome.